Barriers and facilitators to conducting radiotherapy clinical trials: Findings from a UK survey. Issue 2 (March 2023) - Hancock, A.; Hutton, D.; Roberts, D.; Whiteside, L.; Golby, C.; Eccles, C.L.; Turtle, L.; McGinn, S.; Hooton, R.; Fillingham, E.; Hudson, J.; Maguire, M.; et al.
Abstract: Introduction: As an essential component of service delivery, radiotherapy clinical trials were championed within the NHS England service specifications. A call for a 15% increase in research and clinical trial activity, alongside a demand for equity of access for patients with cancer subsequently ensued. National understanding of current radiotherapy clinical trials operational practices is absent, but essential to help establish the current provision required to support the development of a strategic plan for implementation of NHS England's specifications. Methods: A cross-sectional survey was developed by a multi-disciplinary team and distributed to therapeutic radiography clinical trial leads across the UK to ascertain the current provision of radiotherapy clinical trials only, including workforce resources and the trials management processes to establish a benchmark and identify potential barriers, enablers, and opportunities to increase access to clinical trials. Results: Thirty-two complete responses were obtained equating to 49% of the total UK NHS departments and 74% of those departments invited. Four key findings were identified: 1) research strategy and systems, 2) participation and activity in radiotherapy clinical trials, 3) access to clinical trials at alternative departments and 4) facilitators & barriers. Overarchingly a lack of radiotherapy clinical trials strategy or supported processes were apparent across the UK, aggravating existing barriers to trial activity. Conclusion: It is essential for radiotherapy clinical trials to be embedded in to departmental and Trust strategy, this will help to ensure the processes and resources required for trial delivery are not only in place, but also recognised as imperative and important for patients with cancer as radiotherapy treatment delivery. Implications for practice: Failure to address the barriers or build upon the facilitators may result in UK radiotherapy departments facing challenges in achieving the 15% increase in radiotherapy clinical trial activity.